Tanggung Jawab dan Peran Orang Tua Terhadap Pendidikan Anak Dalam Pandangan Islam - Rahmat Hidayat (Al Hikmah: Journal of Education, 2020)
Parents have an important role as child educators, which is a mandate given by God. Parents have an obligation to educate their children to be righteous children. Children who always believe and fear Allah SWT. Islamic education awakens the spiritual strength and willingness of children both in terms of morals and religion. This research is qualitative in nature using the type of library research (Library Research). Data analysis techniques using content analysis methods (content analysis). It is hoped that parents in coaching the family and planting education in the family for their children can give birth to a generation of nations with noble character and character.Orang tua memiliki peranan penting sebagai pendidik anak merupakan amanah yang diberikan Tuhan. Orang tua mempunyai kewajiban untuk mendidik anaknya menjadi anak yang shalih. Anak yang senantiasa beriman dan bertakwa kepada Allah SWT. Pendidikan Islam membangkitkan kekuatan dan kesediaan spiritual anak baik dari segi akhlak maupun agamanya. Penelitian ini bersifat kualitatif menggunakan jenis penelitian kepustakaan (Library Research). Teknik analisis data dengan menggunakan metode analisis isi (content analysis). Diharapkan orang tua dalam pembinaan di keluarga dan penananam pendidikan dalam keluarga terhadap anak dapat melahirkan generasi bangsa yang berakhlak dan berkarakter mulia.